2020
DOI: 10.1093/neuros/nyaa049
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgical Randomized Trials in Low- and Middle-Income Countries

Abstract: BACKGROUND The setting of a randomized trial can determine whether its findings are generalizable and can therefore apply to different settings. The contribution of low- and middle-income countries (LMICs) to neurosurgical randomized trials has not been systematically described before. OBJECTIVE To perform a systematic analysis of design characteristics and methodology, funding source, and interventions studied between trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 30 publications
(33 reference statements)
1
28
0
Order By: Relevance
“…While neurosurgery is in its infancy in many LMICs the development of relevant guidelines is increasingly important. 8 However, LMICs still do not have sufficient evidence to inform neurosurgical practice and improve health. 30 Neurosurgeons in this study understood that research was integral to improving health outcomes 10 31 and for many drove them to conduct research to affect care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While neurosurgery is in its infancy in many LMICs the development of relevant guidelines is increasingly important. 8 However, LMICs still do not have sufficient evidence to inform neurosurgical practice and improve health. 30 Neurosurgeons in this study understood that research was integral to improving health outcomes 10 31 and for many drove them to conduct research to affect care.…”
Section: Discussionmentioning
confidence: 99%
“…29 In the context of advancing neurosurgical technologies funding becomes even more important and more must be done to increase investment in research. 8 Prioritisation of journal publication over improved policy and practice are considered poor incentives to impactful research. 10 Neurosurgeons in this study were aware of both favourable and unfavourable consequences of mandatory research; increasing capacity, while increasing low impact designs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fellows have contributed significantly to the global neurosurgery academic community, presenting their research at international conferences such as the International Conference for Recent Advances in Neurotraumatology (ICRAN) and publishing in highly reputable journals like NEUROSURGERY, Frontiers in Neurology, and World Neurosurgery (13)(14)(15)(16). They perform most of the research activities while based in Colombia in different centers in a broad level of resource availability.…”
Section: Researchmentioning
confidence: 99%
“…A recent review to identify randomised trials of neurosurgical procedures used in cranial and spinal neurosurgical practice found only 8.8% of studies (excluding China) were LMIC-led studies. 8 LMICs need to develop an evidence base that is relevant to the treatments and interventions accessible to them. 3 7 Nurturing an environment that promotes high-quality neurotrauma research is a fundamental part of this.…”
Section: Introductionmentioning
confidence: 99%